Antenatal Nutritional Supplementation and Autism Spectrum Disorders in the Stockholm Youth Cohort: Population-based Cohort Study. Issue 2 (June 2018) - DeVilbiss, E.A.; Magnusson, C.; Gardner, R.M.; Rai, D.; Newschaffer, C.J.; Lyall, K.; Dalman, C.; Lee, B.K.
Abstract : ( BMJ . 2017;359:j4273) Previous research has suggested that autism spectrum disorders (ASD) may develop antenatally. Maternal nutrition affects neurodevelopment and could be a factor affecting the risk of developing ASD. Population-based studies, however, have produced conflicting results. Studies from the United States and Norway found that maternal folic acid supplementation around the time of conception and during early pregnancy decreased the risk of ASD. A Danish study, though, did not find an association between folic acid or multivitamin supplementation and the risk of ASD. The aim of this population-based cohort study was to establish the association between maternal nutritional supplementation and the risk of ASD with and without intellectual disability in offspring.